THE ECOLOGICAL PROBLEMS OF CENTRAL ASIA AND THE WAYS TO ELIMINATE THEM (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The article analyzes the environmental problems of Central Asia and ways to overcome them. Particular attention is paid to the historical aspects of the emergence of environmental crises in the region, their impact on socio-economic development, as well as modern approaches to solving these problems. The prospects for using international experience in developing sustainable environmental strategies aimed at restoring and preserving the region's natural resources were considered. The importance of interstate cooperation and the introduction of innovative technologies for ensuring environmental stability in Central Asia is emphasized.